Complementary Use of Super-Resolution Imaging Modalities to Study the Nanoscale Architecture of Inhibitory Synapses - Gookin, Sara E.; Taylor, Matthew R.; Schwartz, Samantha L.; Kennedy, Matthew J.; Dell’Acqua, Mark L.; Crosby, Kevin C.; Smith, Katharine R. (Frontiers in Synaptic Neuroscience, 2022)
The nanoscale architecture of synapses has been investigated using multiple super-resolution methods, revealing a common modular structure for scaffolds, neurotransmitter receptors, and presynaptic proteins. This fundamental organization of proteins into subsynaptic domains (SSDs) is thought to be important for synaptic function and plasticity and common to many types of synapses. Using 3D super-resolution Structured Illumination Microscopy (3D-SIM), we recently showed that GABAergic inhibitory synapses exhibit this nanoscale organizational principle and are composed of SSDs of GABAA receptors (GABAARs), the inhibitory scaffold gephyrin, and the presynaptic active zone protein, RIM. Here, we have investigated the use of 3D-SIM and dSTORM to analyze the nanoscale architecture of the inhibitory synaptic adhesion molecule, neuroligin-2 (NL2). NL2 is a crucial mediator of inhibitory synapse formation and organization, associating with both GABAARs and gephyrin. However, the nanoscale sub-synaptic distribution NL2 remains unknown. We found that 3D-SIM and dSTORM provide complementary information regarding the distribution of NL2 at the inhibitory synapse, with NL2 forming nanoscale structures that mirror gephyrin nanoscale architecture.